Evaluation of the Results of Patients Who Were Treated with Laparoscopic Simple Tunnel Hysterosacropexy Method to Prevent Uterine Prolapse: A New Approach - Seker, Erdal; Elci, Evindar (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVES: To evaluate the results of patients with uterine prolapse who underwent laparoscopic simple tunnel hysterosacropexy as uterine protective surgery. In this surgical procedure, the parietal peritoneum which was cut off in traditional surgery is preserved. STUDY DESIGN: Data from women with apical prolapse of stage 2 or higher who underwent laparoscopic simple tunnel hysterosacropexy between October 1, 2017, and March 31, 2019, at the University of Health Sciences Diyarbakır Gazi Yasargil Education and Research Hospital, Diyarbakır, Turkey was retrospectively assessed. Patients were treated with laparoscopic simple tunnel hysterosacropexy; the meshes were anchored to the posterior cervical area, even in the presence of advanced multi-compartment vaginal prolapse. Data on the prolapse stage and urogenital functions were collected through clinical examinations, questionnaires at baseline, and 6 months after the operation. Results were analyzed using Wilcoxon Signed Ranks Test and Based on positive ranks. Data are presented as mean, minimum, maximum or percentage according to variables. RESULT: Overall, 12 women were included in the analysis; the mean follow-up was 6 months. There were significant improvements in the complaints and POP-Q values of patients included in the study. There were not any complications during the intraoperative period and postoperative follow-ups. During the first six-month follow-up, there were not any recurrence of prolapse. The mean operative time was 146 minutes; there were no intraoperative visceral or vascular injuries. There was no recurrence or vaginal erosion. CONCLUSION: In patients with stage 2 and more severe uterine prolapse, laparoscopic simple tunnel hysterosacropexy can be performed without cutting the peritoneum. Since the peritoneum is not cut during the surgery; intestinal injury prevalence and mesh exposure rates are lower.